Deep Brain Stimulation for Amelioration of Cognitive Impairment in Neurological Disorders: Neurogenesis and Circuit Reanimation. Issue 7 (July 2019) - Tsai, Sheng-Tzung; Harn, Horng-Jyh; Lin, Shinn-Zong; Tseng, Guo-Fang; Chen, Shin-Yuan
Acute (e.g., traumatic brain injury or stroke) and chronic (e.g., dementia or Parkinson's disease dementia) neurological disorders that involve cognitive impairment and dysfunctional neural circuits always lead to a dreadful and costly experience for patients and their families. The application of deep brain stimulation for the treatment of neuropsychiatric disorders has shown great potential to modulate pathological neural circuits and trigger endogenous neurogenesis. We summarize several important clinical and translational studies that utilize deep brain stimulation to improve cognition based on the potentiation of neural plasticity and neurogenesis. In addition, we discuss the neuroanatomy and cerebral circuits implicated in such studies as well as the potential mechanisms underlying therapeutic benefits.